Pyridine - Parashar Pandey, Pratima (IntechOpen, 2018)
This book is designed and styled in order to give researchers a vast horizon about pyridine. A deep look in the structural analysis of pyridine provides a base for all the building blocks derived from it and its applications. Pyridines and pyridine moieties are found in many natural products, such as vitamins, coenzymes, alkaloids, many drugs, and pesticides. The book is divided into three parts: the first takes to the introduction, the second part deals with composition of various compounds using heterocyclic ring of pyridine, and the third part discusses about applications of pyridine compounds.